Geotechnical Reconnaissance Findings of the October 30 2020, Mw7.0 Samos Island (aegean Sea) Earthquake - Ziotopoulou, Katerinaa; Ecemiş, Nurhan; Pelekis, Panagiotis; Klimis, Nikolaos; Çetin, Kemal Önder; Altun, Selim; Sezer, Alper; Ecemiş, Nurhan (Springer, 2022)
On October 30, 2020 14:51 (UTC), a moment magnitude (Mw) of 7.0 (USGS, EMSC) earthquake occurred in the Aegean Sea north of the island of Samos, Greece. Turkish and Hellenic geotechnical reconnaissance teams were deployed immediately after the event and their findings are documented herein. The predominantly observed failure mechanism was that of earthquake-induced liquefaction and its associated impacts. Such failures are presented and discussed together with a preliminary assessment of the performance of building foundations, slopes and deep excavations, retaining structures and quay walls. On the Anatolian side (Turkey), and with the exception of the Izmir-Bayrakli region where significant site effects were observed, no major geotechnical effects were observed in the form of foundation failures, surface manifestation of liquefaction and lateral soil spreading, rock falls/landslides, failures of deep excavations, retaining structures, quay walls, and subway tunnels. In Samos (Greece), evidence of liquefaction, lateral spreading and damage to quay walls in ports were observed on the northern side of the island. Despite the proximity to the fault (about 10 km), the amplitude and the duration of shaking, the associated liquefaction phenomena were not pervasive. It is further unclear whether the damage to quay walls was due to liquefaction of the underlying soil, or merely due to the inertia of those structures, in conjunction with the presence of soft (yet not necessarily liquefied) foundation soil. A number of rockfalls/landslides were observed but the relevant phenomena were not particularly severe. Similar to the Anatolian side, no failures of engineered retaining structures and major infrastructure such as dams, bridges, viaducts, tunnels were observed in the island of Samos which can be mostly attributed to the lack of such infrastructure.
Keywords: Lateral spreading; Liquefaction; Seismic performance; Samos earthquake